Four Non-functional FUT1 Alleles Were Identified in Seven Chinese Individuals with Para-Bombay Phenotypes - Wei LIANG; Feng CAI; Liang YANG; Zhe ZHANG; Zhicheng WANG (Iranian Journal of Public Health, 2018)
Background: The para-Bombay phenotype is characterized by a lack of ABH antigens on red cells, but ABH substances are found in saliva. Molecular genetic analysis was performed for seven Chinese individuals serologically typed as para-Bombay in Blood Station Center of Ningbo, Zhejiang Province, Ningbo, China from 2011 to 2014.